ESG, Audit Quality, and Political Connections on Firm Value: The Mediating Role of Leverage and Profitability - Restuningsih, Jumi; Gusni, Gusni (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This study investigates the impact of environmental, social, and governance (ESG) practices, audit quality, and political ties on firm value, with leverage and profitability as mediators. Using data from 18 ESG Leader firms (2021–2024) and analyzed through Structural Equation Modeling (SEM) with SmartPLS 4, the research explores both direct and indirect effects. Results show ESG and audit quality do not directly affect firm value but become significant when mediated by leverage and profitability. Political connections negatively influence firm value directly but exert a positive effect indirectly through financial performance. Leverage and profitability emerge as key mediators, explaining much of the variation in firm value and underscoring the role of financial mechanisms in transmitting non-financial factors. The study contributes originality by integrating governance, audit quality, and political connections with financial performance offer a more comprehensive interpretation of firm value.